Contiguous ABCD1 DXS1357E deletion syndrome: Report of an autopsy case. Issue 3 (21st September 2012) - Iwasa, Mitsuaki; Yamagata, Takanori; Mizuguchi, Masashi; Itoh, Masayuki; Matsumoto, Ayumi; Hironaka, Mitsugu; Honda, Ayako; Momoi, Mariko Y.; Shimozawa, Nobuyuki
<x xml:space="preserve">Abstract</x> Contiguous ABCD1 DXS1357E deletion syndrome (CADDS) is a contiguous deletion syndrome involving the ABCD1 and DXS1357E/BAP31 genes on Xq28. Although ABCD1 is responsible for X‐linked adrenoleukodystrophy (X‐ALD), its phenotype differs from that of CADDS, which manifests with many features of Zellweger syndrome (ZS), including severe growth and developmental retardation, liver dysfunction, cholestasis and early infantile death. We report here the fourth case of CADDS, in which a boy had dysmorphic features, including a flat orbital edge, hypoplastic nose, micrognathia, inguinal hernia, micropenis, cryptorchidism and club feet, all of which are shared by ZS. The patient achieved no developmental milestones and died of pneumonia at 8 months. Biochemical studies demonstrated abnormal metabolism of very long chain fatty acids, which was higher than that seen in X‐ALD. Immunocytochemistry and Western blot showed the absence of ALD protein (ALDP) despite the presence of other peroxisomal proteins. Pathological studies disclosed a small brain with hypomyelination and secondary hypoxic‐ischemic changes. Neuronal heterotopia in the white matter and leptomeningeal glioneuronal heterotopia indicated a neuronal migration disorder. The liver showed fibrosis and cholestasis. The thymus and adrenal glands were hypoplastic. Array comparative genomic hybridization (CGH) analysis suggested that the deletion was a genomic rearrangement in the 90‐kb span starting in DXS1357E/BACP31 exon 4 and included ABCD1, PLXNB3, SRPK3, IDH3G and SSR4, ending in PDZD4 exon 8. Thus, the absence of ALDP, when combined with defects in the B‐cell antigen receptor associated protein 31 (BAP31) and other factors, severely affects VLCFA metabolism on peroxisomal functions and produces ZS‐like pathology.